A quick method for producing biodiesel from soy sauce residue under supercritical carbon dioxide. (April 2019) - Xiang, Cheng; Liu, Si Yu; Fu, Yan; Chang, Jie
Abstract: This paper proposed a novel method for the production of biodiesel from soy sauce residue under supercritical carbon dioxide for the first time. The effect of several parameters, such as the size of raw material, reaction pressure, temperature, time, and methanol/oil molar ratio were carefully optimized by single-factor experiments. The results showed that the optimized parameters were particle size 60 meshes, reaction pressure 16 MPa, temperature 100 °C, time 180min and methanol/oil molar ratio 35:1. Under this optimal conditions, biodiesel yield is as high as 96.21%. Furthermore, in order to better understand the advantages of this process, the mechanism and result of this process were compared with existing technology. The findings of this paper demonstrated that the soy sauce residue which was commonly considered as a waste can be efficiently converted to biodiesel by this method. Graphical abstract: Highlights: The raw material is an oil-rich residue rather than common vegetable oil resources. The reaction conditions are mild under supercritical carbon dioxide system. The highest biodiesel yield was achieved at 100 °C and 16 MPa after 180 min. The possible reaction mechanism was proposed and compared with other processes.